Effect and sustainability of part-time occlusion therapy for patients with anisometropic amblyopia aged ≥8 years. Issue 9 (7th June 2010) - Hwang, D J; Kim, Y J; Lee, J Y
Abstract : Aims: To study the effect and long-term sustainability of part-time occlusion therapy for anisometropic amblyopia after 8 years of age. Methods: A total of 41 anisometropic amblyopes aged ≥8 years were analysed. In six patients, best-corrected visual acuity (BCVA) of amblyopic eye improved more than two lines within 2 weeks of full-time spectacle wear. The remaining patients were assigned to perform part-time patching during out-of-school hours. Long-term results were assessed in patients who were observed over 1 year after the end of the treatment. Results: Among 35 patients, four dropped out, refusing further treatment, and one changed to atropine penalisation. The part-time patching schedule was completed in 30 patients. 90% of patients (27/30) complied well. Mean BCVA in the amblyopic eye improved significantly (p<0.001), and 96.7% of patients (29/30) achieved the final BCVA of 0.1 logMAR or better. In long-term results, 87% preserved the BCVA of 0.1 logMAR or better. None of four dropouts achieved the BCVA of 0.1 logMAR or better in long-term results even on the continuous spectacle wear. Conclusions: The part-time occlusion treatment in school-aged amblyopes, which had been carried out after school hours, was successful and the effect was sustained in most cases.